A comparative study of the labour outcomes following induction with oral misoprostol and oxytocin in pregnant women with PROM - Disha Ajila; Ritu Sharma A (New Indian Journal of OBGYN, 2023)
Objectives: This retrospective study was conducted to assess and compare the efficacy of oral misoprostol and intravenous oxytocin in the induction of labour after PROM. Materials and method: A total of 106 patients with singleton term pregnancy with PROM were included in the misoprostol and oxytocin groups. Misoprostol and oxytocin were administered in the standard doses. Close monitoring of the maternal and fetal status and progress of labour was done. In cases of failed induction, cesarean section was performed. The outcome was recorded. Results and observations: Both the groups were comparable in terms of demographic and baseline parameters. The induction to delivery time was significantly shorter in the misoprostol group (P value <0.001). The cesarean section rates were comparable in both the groups. There was no incidence of intrapartum complications in any group. The fetal outcome, in terms of APGAR scores and NICU admissions, was also comparable. Conclusion: Oral misoprostol is a safe and effective alternative to oxytocin, especially in cases of unfavourable cervix.